The association of urolithiasis and androgenetic alopecia. (2nd January 2016) - Resorlu, Mustafa; Sancak, Eyup Burak; Uysal, Fatma; Arslan, Muhammet; Diri, Akif; Adam, Gurhan; Akbas, Alpaslan; Sariyildirim, Abdullah; Gulpinar, Murat Tolga; Resorlu, Berkan
Abstract: Objectives : The objective of this study is to investigate whether patients with androgenetic alopecia were at risk in terms of urinary system stone disease. Patients and methods : Patients with no baldness (Hamilton–Norwood Scala [HNS] stage I) were categorized as Group I, those with hair loss in the frontal region (HNS stages II, III, IIIa, and IVa) as Group II, those with hair loss in the vertex region (HNS stage III-vertex, V) as Group III and those with hair loss in both vertex and frontal regions (HNS stages IV, Va, VI, and VII) as Group IV. Patients in all groups were compared in terms of presence of stone, and the presence of any association between alopecia and urolithiasis, with common etiological risk factors, was investigated. Results : Three hundred and two male patients were included in the study. The presence of urolithiasis was detected in 28.9% of patients in Group I; 26.5% of Group II; 36.9% of Group III; and 44.4% of Group IV ( p = 0.085). Among patients aged under 60, urinary stone disease was detected in 30.8% of patients in Group I; 26.4% of Group II; 41.2% of Group III; and 53.8% of Group IV ( p = 0.001). In patients aged over 60, urolithiasis was detected in 12.5% of patients in Group I; 26.9% of Group II; 32.2% of Group III; and 37.8% of Group IV ( p = 0.371). Conclusions : We determined a significant correlation between vertex pattern and total alopecia with urolithiasis in patients younger than 60 years old.